Debt Maturity, Risk, and Asymmetric Information - Espinosa-Vega, Marco (IMF Working Papers; Working Paper ;, 2005)
We test the implications of Flannery's (1986) and Diamond's (1991) models concerning the effects of risk and asymmetric information in determining debt maturity, and we examine the overall importance of informational asymmetries in debt maturity choices. We employ data on over 6,000 commercial loans from 53 large U.S. banks. Our results for low-risk firms are consistent with the predictions of both theoretical models, but our findings for high-risk firms conflict with the predictions of Diamond's model and with much of the empirical literature. Our findings also suggest a strong quantitative role for asymmetric information in explaining debt maturity.